Influence of First-Time Mothers' Early Employment on Severe Early Childhood Caries in Their Child - Kamila Plutzer; Marc J. N. C. Keirse (Hindawi Limited, 2012)
Aim. To examine whether mothers' early employment status is related to the development of severe early childhood caries in their child. Methods. Questionnaire survey of 429 first-time mothers in metropolitan Adelaide, South Australia, and dental examinations of their child at 20 months of age. Results. At months of age, 5.6% of children exhibited caries defined as one or more demineralized or cavitated lesions on the upper incisors. Of the mothers, 52.2% had no paid employment, 39.6% were part-time and 8.2% full-time employed. Overall, mothers' participation in the workforce had no influence on the frequency of severe early childhood caries in their child, but there was a significant interaction with family structure. For mothers without employment there was no difference between single, and two-parent families, but children with an employed single mother more frequently had caries than those with a working mother in a two-parent family (). However, there were no significant differences in children's reported general health. Conclusions. The data indicate a need to explore strategies that may assist single mothers and especially those in the workforce to prevent severe early childhood caries in their child.